2016
DOI: 10.3389/fmicb.2016.00274
|View full text |Cite
|
Sign up to set email alerts
|

Epimural Indicator Phylotypes of Transiently-Induced Subacute Ruminal Acidosis in Dairy Cattle

Abstract: The impact of a long-term subacute rumen acidosis (SARA) on the bovine epimural bacterial microbiome (BEBM) and its consequences for rumen health is poorly understood. This study aimed to investigate shifts in the BEBM during a long-term transient SARA model consisting of two concentrate-diet-induced SARA challenges separated by a 1-week challenge break. Eight cows were fed forage and varying concentrate amounts throughout the experiment. In total, 32 rumen papilla biopsies were taken for DNA isolation (4 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 55 publications
6
45
0
Order By: Relevance
“…Of the ruminal microbial communities, bacteria in the rumen fluid and those attached to feed particles have attracted considerable research interest, but comparatively less is known about bacteria attached to the rumen wall, commonly known as epimural bacteria. In recent years, a few studies have been published describing the bovine epimural bacterial microbiome (BEBM) using high-throughput sequencing methods (Mao et al, 2015;Liu et al, 2016;Wetzels et al, 2016), but each have shown low sequence similarity between detected phylotypes and best type strain hits. From the host perspective, the BEBM is the first contact between the rumen environment and the rumen epithelium, competing with adherent and putative pathogenic microorganisms (Kamra, 2005;Khafipour et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Of the ruminal microbial communities, bacteria in the rumen fluid and those attached to feed particles have attracted considerable research interest, but comparatively less is known about bacteria attached to the rumen wall, commonly known as epimural bacteria. In recent years, a few studies have been published describing the bovine epimural bacterial microbiome (BEBM) using high-throughput sequencing methods (Mao et al, 2015;Liu et al, 2016;Wetzels et al, 2016), but each have shown low sequence similarity between detected phylotypes and best type strain hits. From the host perspective, the BEBM is the first contact between the rumen environment and the rumen epithelium, competing with adherent and putative pathogenic microorganisms (Kamra, 2005;Khafipour et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The severity and duration of SARA conditions are particularly relevant for rumen health (Khafipour et al, 2009;Schwaiger et al, 2013). Recent research of our team observed that intermittent SARA conditions are stronger than persistent SARA conditions, likely because the rumen and its microbiota have less chance to adapt and the VFA are less absorbed across the reticulorumen wall Qumar et al, 2016;Wetzels et al, 2016). The latter is a major concern, as VFA absorption is essential for the regulation of the intraruminal pH and the alleviation of SARA conditions (Aschenbach et al, 2011;Schwaiger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Two OTUs (6 and 34) with reduced abundance found in samples supplemented with Sucram ® were classified as potential sulfate-reducing bacteria (SRB) within the Desulfobulbus genus and were related to Desulfobulbus oligotrophicus (sequence similarity >97% using NCBI BLAST [46, 47]. SRB are commonly found within the gastrointestinal tract of ruminants [48] and particularly at the rumen wall [44, 49] and are known to reduce SO 3 2− to SO 4 2− and H 2 S [50]. This leads to the reduction of available metabolic hydrogen generated in cellulose and SCFA metabolism [47, 51].…”
Section: Discussionmentioning
confidence: 99%